Symbiotic care between residents in service-integrated housing. Issue 3 (12th August 2019) - Meyer, Desneige; Martin, Wanda; Funk, Laura M.
Abstract : Purpose: Sustainable solutions for meeting the physical, emotional and social health care needs of individuals may be realized by shifting the care landscape; for instance, through innovative models of service-integrated housing (SIH). By diversifying populations in these settings, care recipients can choose to engage their skills and abilities toward assisting co-residents, and vice versa as a form of symbiosis. The purpose of this paper is to define attributes of the concept and practice of symbiotic care. Design/methodology/approach: The authors drew on firsthand field experience and secondary data from a literature review to conduct a conceptual derivation and analysis, using Walker and Avant's methodology. The term symbiotic mutualism was derived from the field of biology as an analogy for care exchanged between non-peer co-residents. Attributes, antecedents and consequences of symbiotic care were identified and illustrated using model, borderline and contrary case descriptions. Findings: Four defining attributes of symbiotic care were identified: first, cohabitation: care recipients live closely together in SIH settings. Second, non-peer: co-residents have distinct, complementary needs and abilities. Third, mutualism: co-residents experience mutually significant benefits as a result of the activities of their co-residents. Fourth, agency-sponsored: the professional SIH agency or organization attends to unmet resident needs. Research limitations/implications: Symbiotic care is a relatively rare phenomenon for which little research exists. This analysis provides a starting point for empirical research, policy and program development and critical evaluation. Originality/value: This paper fills a wide gap in the research literature and offers important terminology. It is the first to define the attributes of symbiotic care.